Results of the Universal 2 Prosthesis in Noninflammatory Osteoarthritic Wrists - Brinkhorst, M. E.; Selles, R. W.; Dias, J. J.; Singh, H. P.; Feitz, R.; Moojen, T. M.; Hovius, S. E. R. (Journal of Wrist Surgery, 2018)
Background/Purpose Many treatment options are available for wrist osteoarthritis, with the objective of decreasing pain and preserving function. In later stages when midcarpal and radiocarpal osteoarthritis occur, two choices remain: total wrist arthrodesis or total wrist arthroplasty. The purpose of this study is to present the short-term functional changes following total wrist arthroplasty with the Universal 2 total wrist system (Integra Life Sciences) in patients with noninflammatory wrist osteoarthritis.Patients and Methods Patients with severe noninflammatory wrist osteoarthritis were assessed preoperatively, 6 and 12 months after surgery using a range of motion, grip strength, pain, and the disabilities of the arm, shoulder, and hand (DASH) score. The additional assessment was performed after 1 year for a range of motion using a biaxial electrogoniometer, grip strength, DASH, and the Michigan hand questionnaire.Results All range of motion directions and grip strength did not change from preoperative values. The DASH score improved from 53 preoperatively to 14 during latest follow-up. Median patients' satisfaction score decreased with approximately 20 points during the last follow-up.Conclusion The relatively good DASH score combined with the partly maintained wrist range of motion indicates that reconstruction with the Universal 2 total wrist prosthesis should be considered in patients with end-stage noninflammatory wrist osteoarthritis.Level of Evidence Level IV, therapeutic study.
Keywords: posttraumatic osteoarthritis; scaphoid nonunion advanced collapse; scapholunate advanced collapse; total wrist arthroplasty; Universal 2 total wrist prosthesis